Efektivitas Sistem Akuntasi Penerimaan Kas pada Bank Muamalat KCP Bone - Sudirman, Sudirman; Awaliyah, Lusi; Irmawati, Ika; Harun, Salmah; Idris, M. Abduh (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In the constantly evolving digital age, the information assurance system has to deal with a lot of new challenges and opportunities. Due to the importance of data accuracy and timeliness, businesses must invest in reliable technologies and instruct their staff in maximize the use of open-source information systems. The purpose of this qualitative research study is to assess the information system's uptime for the Bank Muamalat KCP Bone. To achieve this goal, the researcher used documentation, observation, and interview to gather data. The study's findings indicate that the Bank Muamalat KCP Bone's kas redemption system functions effectively. This is because Otoritas Jasa Keuangan has tightened rules for operational systems. In addition, the information retrieval system, which is based on the Mardiasmo theory and has two components—results and objectives—is also highly effective.